Mechanistic studies on regulation of the activity of GPI-anchored serine protease testisin - WAN Jiahui; ZHOU Aiwu (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To explore the activation methods and activity regulation mechanisms of the testisin zymogen in vitro, laying a foundation for further research on the physiological functions of testisin in organisms.Methods·The eukaryotic expression plasmid for the mouse-derived testisin (mTN) zymogen was constructed through full-gene synthesis and subsequently transfected into eukaryotic HEK293S cells for expression. Purified recombinant testisin protein was obtained through methods such as nickel ion affinity chromatography. Site-directed mutagenesis was performed on the activation site and active center of the zymogen, and the activation mechanism of testisin was analyzed through enzymatic activity assays. Additionally, the activation rate of the protein was determined by altering the incubation conditions of the zymogen. The self-cleavage site of the protease was identified by using Edman degradation and site-directed mutagenesis. Finally, the regulatory mechanism of protease activity was examined by analyzing the proteolytic rate of the protein towards its substrates.Results·The recombinant mTN zymogen was expressed in eukaryotic HEK293S cells, and high-purity, uniform recombinant protein was obtained through a two-step purification process. This protein was found to remain stable under acidic conditions but underwent self-activation in neutral or alkaline environments. The rate of activation was influenced by factors such as pH value and temperature. The self-activation process required on the integrity of the enzyme's activation site, Arg46, and its active center, Ser240. Additionally, the self-activation of the recombinant mTN zymogen was often accompanied by the self-cleavage at the 170/175 loop on the molecular surface, but this self-cleavage did not affect the activity of testisin. Furthermore, the optimal reaction pH for activated mTN was 8.0, with the protein remaining relatively stable near this pH. The optimal reaction temperature was 50 ℃, while the protein was best stored at temperatures below 30 ℃. Zn2+ and Ca2+ were found to significantly inhibit mTN activity.Conclusion·An effective method for the preparation of recombinant mTN zymogen is successfully established, and it is discovered that the recombinant mTN undergoes self-activation and self-cleavage in vitro.